New data about Chiropterofauna of the “Monte Pellegrino” Nature Reserve (Palermo, Italy) - Lo Nigro, Marta; Rallo, Angelica; Provinzano, Giovanni; Vanisova, Elena; Lo Valvo, Mario (E3S Web of Conferences, 2021)
This work increase the knowledge related to bat fauna present in the “Monte Pellegrino” Nature Reserve in the Palermo municipality. The acoustic sampling took place in the summer/autumn season using the D500X Bat detector in 22 samples. The identified signals were attributed to 8 species and one genus. The Taxa with the most passes in the reserve are: Tadarita teniotis followed by Pipistrellus kuhlii, Hypsugo savii (100% of Costancy), Pipistrellus pygmaeus, Pipistrellus pipistrellus, Plecotus sp., Miniopterus schreibersii and last with a single recording Rhinolophus ferrumequinum and Rhinolophus hipposideros. The dendrogram of similarity shows 3 distinct bats cenosis. Two samples present intense activity in almost all time slots and three samples, close to each, show a peak increase in the intermediate time slots for the three most abundant species. The analysis carried out on the environmental preferences shows that among the 13 Corine Land Cover (CLC) habitats, the highest number of passes is recorded in Artificial lakes (code 5122), Orchards (code 222) and Arid limestone grassland (code 3211). The Arid limestone grassland habitat (code 3211) has the highest Shannon Index value, while the Mastic stain habitat (code 32312) has the lowest diversity value. The dendrogram of similarity shows two clusters. In the first there are Gorse (code 32231), Mediterranean scrub (code 31111), Orchards (code 222), Mosaic of agricultural plots (code 242), while the second cluster contains the remaining habitats.